Exploring commensal streptococci to prevent Streptococcus pneumoniae colonization - Handem, Sara (2023)
Several Streptococcus species colonize various niches of the upper respiratory tract (URT). Among the over 50 distinct streptococcal species, some are considered opportunistic pathogens whereas others are considered commensals. Nevertheless, many co-exist in the same niche, having evolved numerous strategies to compete and survive.